Nationality and sociocultural factors influence athlete development and sport outcomes: Perspectives from United States and Austrian youth alpine ski racing - DeCouto, B. S.; Cowan, R. L.; Fawver, B.; Müller, E.; Steidl-Müller, L.; Pötzelsberger, B.; Raschner, C.; Lohse, K. R.; Williams, A. M. (Journal of Sports Sciences, 2021)
Geographical regions possess distinct sporting cultures that can influence athletic development from a young age. The United States (US) and Austria both produce elite alpine ski racers, yet have distinct sport structures (i.e., funding, skiing prominence). In this exploratory study, we investigated sport outcomes and psychological profiles in adolescent alpine ski racers attending skill development academies in the US (N= 169) and Austria (N= 209). Sport participation and psychological questionnaires (mental toughness, perfectionism, grit, coping, burnout) were administered to athletes. In Austria, athletes participated in fewer extracurricular sports, began competing and training younger, and accumulated less practice hours than athletes in the US. Athletes in the US reported greater burnout than athletes in Austria. Finally, in the US, women accumulated more practice hours and experienced more parental pressure than men, while men accumulated more practice hours in Austria. Austria`s skiing-centric sport culture may encourage athletes to fully immerse into the sport, contributing to positive psychological outcomes. Reduced sport opportunities in the US beyond educational institutions may pressure athletes to practice more to ensure continued competitive skiing. Stressors for sport participation will be unique to gender in each country though, given their implicit gender stigmas for sport participation.